The sleep of Behemoth: disputing peace and violence in medieval Europe, 1000/1200 - Malegam, Jehangir Yezdi (Cornell University Press, 2013)
Millennial reform and revisions of peace -- The papal reform : peace espoused and repudiated -- False sacraments : violence, captivity and insurrection -- Dueling sacraments : the communion of Judas Iscariot -- Mediations between self and society : peace, discretion and discipline -- Peacemaking, ecclesiology and evangelism -- Communes : inversions of peace -- Disciplining Behemoth : provisions for secular peace